INITIATION OF THE FORMATION OF FIT VILLAGE AS AN EFFORT TO PREVENT METABOLIC DISEASES IN SINGOTRUNAN VILLAGE, BANYUWANGI - Herawati, Lilik; Argarini, Raden; Irwadi, Irfiansyah; Setiawan, Hayuris Kinandita; Wiyasihati, Sundari Indah; Azmy, Ulul (Universitas Airlangga, 2024)
Metabolic disease is an epidemic phenomenon that affects both men and women from various ages, ethnic, and socio-economic groups. The term metabolic disease itself is an umbrella term that includes, among others: hypertension, type 2 diabetes mellitus, hyperlipidemia, obesity, and non-alcoholic fatty liver disease. Lifestyles such as poor nutrition, physical activity, and habits are risk factors that can increase the incidence of metabolic disease. Therefore, prevention of metabolic diseases is necessary, including for ordinary people. Metabolic disease, namely hypertension, is in 3rd place and diabetes is in 10th place, the most common disease suffered by residents of Singotrunan Village, Banyuwangi. In this regard, it is important to make efforts to prevent metabolic disease and even death due to complications from metabolic disease. This community service program is designed to create a fit village as a sustainable healthy lifestyle, initiated through health checks for screening, exercise training, education and discussions as encouragement to do regular exercise. The participants' pre-test and post-test results showed a significant increase in their level of knowledge (p=0.01). The results of the participant satisfaction test showed that 80.9% of participants said they were very satisfied and the rest (19.1%) said they were satisfied. It is hoped that the PKM activity to initiate a fit village in Singotrunan Village, Banyuwangi will provide motivation for residents to exercise regularly and can become a model village for residents of other areas.